Effects of exposure to ozone and water stress on the following season's growth of beech (Fagus sylvatica L.) - Pearson, M (The New phytologist, 1994)
Bud break and growth of beech trees were measured during the growing season of 1992. The trees had previously been exposed, through the growing season of 1991, to one of four treatments: (1) episodic ozone for 128 d, total dose = 46-3 ppm h; (2) air purified by filtration through Purified and charcoal; (3) ozone together with a period of water shortage: (4) filtered air with a period of water shortage. Despite uniform growth conditions during 1992. the previous water stress treatment caused bud break to begin slightly earlier, but the rates of shoot growth and the length of the first flush branches were reduced (40%). In well-watered plants ozone caused a reduced Tate of shoot growth during the first week after bud break. The total amount of growth during 1992 was shown to be reduced (36%) by the previous water stress treatment, In the case of the well-watered trees, exposure to ozone in the previous year reduced the amount of new growth by 17%, which was the result of reduced internal expansion. When ozone was combined with water stress, there was no further reduction in the amount of new growth, but there was a fall in the number of internodes relative to water-stressed plants grown in filtered air. Ozone and water stress applied singly reduced growth. A combination of the two stresses, however, caused no additional reduction in growth, but reduced the number of internodes. The possible implications of the aftereffects of these stresses are discussed in relation to reduced productivity and canopy structure